The effect of emotional marketing in enhancing customer insight: بحث استطلاعي لاراء عينة من القيادات في شركة كالة للمنتجات الغذائية / كربلاء المقدسة - Aabeed Muhsen, Nihaya; Jabur Aalwan, Hasan (Iraqi Journal for Administrative Sciences, 2024)
The impact of emotional marketing in enhancing customer insight : The research aims to determine the effect of emotional marketing in enhancing the customer's insight at the sample level of the Kalah Food Products Company, based on a major problem that the company's management is not interested in emotional marketing in enhancing the customer's insight. The questionnaire was adopted to collect data from the company's sample, which amounted to (63) individuals. The research included two main hypotheses, from which several sub-hypotheses emerged. A number of statistical methods were used and a number of conclusions were reached, the most important of which is the company's management has a quick response to the requirements of customers through designing products that meet the needs and desires of customers and according to their preference. For these products, he concluded with a set of recommendations, the most important of which is that the company uses smart practices to reach the customer.